2019
DOI: 10.1111/jfbc.13044
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of betacyanins from agricultural by‐products using pressurized hot water extraction for antioxidant and in vitro oleic acid‐induced steatohepatitis inhibitory activity

Abstract: Pressurized hot water extraction (PHWE) is proposed to recover betacyanins from agricultural by-products (pitaya fruits peels (PFP), red beet stalks (RBS), and cactus pear peels (CPP)). The extraction yield of betacyanins was optimized by response surface methodology. The optimal PHWE conditions were attained and the actual yields of betacyanins under optimal conditions were well matched with the predicted yields.In addition, betacyanin pigment compositions as well as superoxide anion scavenging activity of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Another interesting option to recover betalains from food byproducts is the use of pressurized water extraction. This technology has been recently applied for the extraction of betalains from pitaya fruits peels, red beet stalks, and cactus pear peels . These authors demonstrated that temperature plays a key role in the extraction of betacyanins through pressurized hot water extraction, although the effect of such a variable depends on the matrix.…”
Section: Betalainsmentioning
confidence: 99%
See 4 more Smart Citations
“…Another interesting option to recover betalains from food byproducts is the use of pressurized water extraction. This technology has been recently applied for the extraction of betalains from pitaya fruits peels, red beet stalks, and cactus pear peels . These authors demonstrated that temperature plays a key role in the extraction of betacyanins through pressurized hot water extraction, although the effect of such a variable depends on the matrix.…”
Section: Betalainsmentioning
confidence: 99%
“…Extracts obtained by pressurized hot water extraction method have also proven to have good bioactivities . For instance, red beet stalks and cactus pear peels extracts obtained by pressurized hot water extraction exhibited good superoxide anion scavenging potential.…”
Section: Betalainsmentioning
confidence: 99%
See 3 more Smart Citations